Improving Students’ Reading Comprehension through the RAPQ (Read-Ask-Put-Question) Technique - Maemunah, Siti; Surayya, St. Ayu; Farizi, Zukhruf (Sumber Belajar Sejahtera, 2025)
This classroom action research aimed to improve the reading comprehension skills of eighth-grade EFL students by implementing the Read-Ask-Put-Question (RAPQ) technique at SMP NW Gelanggang during the 2024–2025 academic year. The research followed the standard planning, acting, observing, and reflecting cycle. Seventeen students participated in a one-cycle intervention that integrated the RAPQ technique into regular reading instruction. The technique involved four structured stages: reading the text, identifying and asking about the main idea, paraphrasing the idea using the students’ words, and generating and answering comprehension questions. Data were collected using pre-test and post-test assessments, supported by classroom observations and field notes. Quantitative results showed a significant improvement in students’ reading performance, with the mean score increasing from 8.18 to 17.29. A paired-sample t-test confirmed that this improvement was statistically significant (t (16) = -9.877, p < .001). The results indicate that the RAPQ technique fosters more active, strategic reading by encouraging comprehension monitoring and textual engagement. The study concludes that RAPQ is a practical, student-centered strategy for enhancing reading comprehension in lower secondary EFL contexts, particularly where students have previously relied on teacher-dominated instruction.